140 Rising incidence of cervical adenocarcinoma in the United States – who is most at risk?. (13th November 2020) - Liao, C; Furey, K; Richardson, M; Tran, K; Tian, C; Chan, A; Darcy, KM; Kapp, DS; Cohen, JG; Chan, JK
Abstract : Objective: To observe trends in the incidence of adenocarcinoma (AC) in relation to race and stage at diagnosis. Methods: From 2001 to 2016, incidence rates of Adenocarcinoma of the cervix were calculated from United States Cancer Statistics with Surveillance, Epidemiology and End Results (SEER) Program. SEER*Stat and Joinpoint regression were used to calculate the incidence rate (per 100, 000 women) and average annual percent change (AAPC), adjusted for hysterectomy and pregnancy prevalence data from the Behavioral Risk Factor Surveillance System. Results: Over the 16-year study period, approximately 36, 000 of 200, 000 women with cervical cancer were identified with AC (18.1%). The incidence increased in reproductive-aged women (35–39yo and 40–44yo) with an average annual percent change of 2.0% and 2.4%, respectively; however the incidence decreased for the older cohorts (70–74 and 80+) with -1.6% and -2.5% decrease per year. Intersectionality of race and age demonstrates the highest incidence for White women at 40–44yo (0.56/100, 000). Blacks demonstrate a bimodal age distribution at diagnosis, with peaks at 40–44yo (0.52) and 65–69yo (0.57). Age-adjusted incidence demonstrated that Blacks were more likely to be diagnosed with distant disease as compared to Whites (20.6% vs. 10.4%) and less likely to be diagnosed with local disease (40.4% vs. 59.6%). Conclusion: Reproductive-aged White women have the highest incidence of cervical adenocarcinoma compared to other age and racial groups. However, Blacks are more likely to be diagnosed at more advanced stages of disease.